Comparison of the effects of perioperative and adjuvant chemotherapy on outcomes of operable gastric cancer: a retrospective cohort experience from a tertiary cancer center - Jamshed Ali; Nuzhat Humayun; Shameen Ikram; Muhammad Abu Bakar; Umm-e-Kulsoom; Rizwan Masood Sheikh; admin (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the overall survival and disease-free survival rates with perioperative or adjuvant chemotherapy regimens in operable gastric cancer cases. Method: The retrospective, observational study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised date from January 2015 to December 2020 of operable gastric cancer patients who had perioperative or adjuvant chemotherapy. Overall survival and disease-free survival were evaluated. Data was analysed using SPSS 23. Results: Of the 108 patients in the aga range 27-80 years, 71(65.74%) were males. The overall median age was 49.50 years (interquartile range: 28 years). There were 69(63.88%) patients on perioperative and 39(36.12%) on adjuvant chemotherapy. The probability of 2- and 3-year overall survival was 68.20% and 57.32% in the perioperative group, and 51.09% and 45.43%, respectively, in the adjuvant group. The probability of 2- and 3-year disease-free survival was 55.45% and 49.30% in the perioperative group, while 2-year disease-free survival was 38.39% in the adjuvant group which had no patient reaching the 3-year mark. The median overall survival for the perioperative group was 49.29 months (interquartile range: 44.50 months) and for the adjuvant group it was 28.23 months (interquartile range: 25.00months) (p=0.07). The median disease-free survival was 35.46 months (interquartile range: 38.50 months) for the perioperative group and 10.19 months (interquartile range: 14.00months) for adjuvant group (p=0.16). The difference between the groups was not significant (p>0.05), but there was a trend suggestive of the superiority of perioperative chemotherapy over adjuvant chemotherapy. Conclusion: In operable gastric cancer cases, the difference between the groups was not significant, but there was a trend suggestive of the superiority of perioperative chemotherapy over adjuvant chemotherapy with respect to overall survival and disease-free survival. Key Words: Gastric cancer, Outcomes, Pakistan, Adjuvant chemotherapy, Perioperative chemotherapy, Survival.